Analisis Risiko Kehamilan pada Ibu Hamil di RS Muhammad Zein Kabupaten Belitung Timur - Haryadi, Edward; Harokan, Ali; Zaman, Chairil (Avicenna: Jurnal Ilmiah, 2025)
Background: At Muhammad Zein Hospital for the past 3 years, high-risk pregnancy data was obtained in 2022 as much as 16.37%, in 2023 it increased to 19.5% and in 2024 as much as 24.19%. The high risk of pregnancy in mothers can threaten safety and even the worst thing can happen, namely maternal and infant death. This study aims to determine the Pregnancy Risk Analysis in Pregnant Women at Muhammad Zein Hospital, East Belitung Regency in 2025. Methods: This study was conducted from May 1 to June 1, 2025. The quantitative research design used a cross-sectional approach, where the population in this study was all visits by pregnant women at Muhammad Zein Hospital as many as 385 respondents, with a sample of 80 toddlers. The sampling method in this study was purposive sampling. The inclusion criteria for this study were pregnant women who checked their pregnancy at Muhammad Zein Hospital and were willing to be respondents, while the exclusion criteria for respondents at the time of the interview, there was one thing that prevented them from completing the interview. Data collection used a questionnaire that had been tested for validity and reliability. Data analysis used the chi-square test and logistic regression. Results: The results of the analysis showed a significant relationship between age (pValue = 0.001), pregnancy spacing (pValue = 0.000), knowledge (pValue = 0.015), attitude (pValue = 0.008), access to health services (pValue = 0.008), medical history (pValue = 0.006) and there was no relationship between work (pValue = 0.547) and parity (pValue = 0.400) on pregnancy risk. From the results of the multivariate statistical test, it was obtained that the dominant factor on pregnancy risk was attitude (pValue = 0.012; OR = 9.336) meaning that a mother's bad attitude has a chance of pregnancy risk of 9.336 times compared to a mother's good attitude Conclusion: It is hoped that efforts will be increased to prevent pregnancy risks in pregnant women by providing education, positive attitudes, encouraging mothers to be more active in maintaining their pregnancy, such as routinely carrying out antenatal checks, following the advice of health workers, and avoiding risk factors. Keywords : Pregnancy, Mother, Risk, Attitude